Integrasi dan Kualitas Desain Ruang Mushola pada Café & Coffee Shop: Pengaruhnya terhadap Loyalitas Pengunjung - Nurfadhilah , Ulfaizah Sahril (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
This study aims to examine the integration of prayer spaces (mushola) in the design of cafés and coffee shops as part of supporting facilities and services for Muslim visitors, as well as the influence of mushola availability and design quality on visitor loyalty. The research was conducted through an online survey by distributing questionnaires via social media platforms. A total of 288 respondents participated, selected through purposive sampling with criteria including having visited a café or coffee shop in Makassar City within the last six months, having used the available mushola facilities, and residing in Makassar or surrounding areas. The variables in this study include the availability of mushola facilities, the quality of mushola design, and visitor loyalty. Data were analyzed using descriptive statistics, chi-square tests, and multiple regression analysis with SPSS 26. The findings indicate that both the availability and design quality of mushola facilities in cafés and coffee shops significantly affect visitor loyalty. Respondents showed a strong preference for the presence of mushola when choosing a place and identified key quality aspects such as cleanliness, ablution area accessibility, spatial comfort, completeness of worship equipment, room size, and interior aesthetics as important factors supporting loyalty. These results underscore the importance of inclusive spatial design, particularly in cafés and coffee shops, and offer practical recommendations for designers and business owners to enhance the experience of Muslim customers.